Предмет: Математика,
автор: Аноним
Раскройте скобки и упростите выражение 1)3(a - b) - 2(a +b) 2)4(x + y) + 5(2x - y) 3)2,4(c - 3d) - 1,3(2c -d) 4)-34(13m + n)-14(3m + n)
Ответы
Автор ответа:
0
1) 3(a-b)-2(a+b)=3a-3b-2a-2b=a-5b
2) 4(x+y)+5(2x-y)=4x+4y+10x-5y=14x-y
3) 2,4(c-3d)-1,3(2c-d)=2,4c-7,2d-2,6c+1,3d=-0,2c-5,9d
4)
2) 4(x+y)+5(2x-y)=4x+4y+10x-5y=14x-y
3) 2,4(c-3d)-1,3(2c-d)=2,4c-7,2d-2,6c+1,3d=-0,2c-5,9d
4)
Автор ответа:
0
спс
Автор ответа:
0
спасибо
Похожие вопросы
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: bottovladimir6d
Предмет: Литература,
автор: Аноним
Предмет: Алгебра,
автор: generationgp
Предмет: Математика,
автор: Max220